Immobilization of free-ranging moose (Alces alces) with medetomidine-ketamine and remobilization with atipamezole - Arnemo, Jon M. (Rangifer, 1995)
Seventeen free-ranging moose {Alces alces) (2 adult males, 13 adult females and 2 female calves) were immobilized with a combination of medetomidine hydochloride (MED) and ketamine hydrochloride (KET) in early autumn (August-September). Drugs were administrated with plastic projectile syringes fired from a dart gun, either from a car or by approaching the animals on foot. MED at 30 mg/adult and 15 mg/calf in combination with KET at 400 mg/adult and 200 mg/calf induced complete immobilization with sternal or lateral recumbency and loss of the corneal reflex in all individuals. The mean ± SD time from darting to when the animals were found was 18.3 ± 8.7 min for adults and the mean distance covered by these animals between darting and recumbency was 320 + 200 m. No side effects of clinical significance were detected and registration of the rectal temperature (38.8 ± 0.5°C), heart rate (44 ± 7 beats/min), respiratory rate (31 ±20 breaths/min) and relative arterial oxygen saturation (89 ± 3 %, n=8) during immobilization in adults showed that these physiological parameters were within the safe ranges established for moose. Blood samples from adults were analyzed for 17 haematological and 33 serum biochemical constituents and the results were compared to corresponding values found in moose immobilized with etorphine (ETO). Although the lower levels (p<0.05) found for haematocrit, red blood cells, haemoglobin and Cortisol in the MED-KET group may indicate a difference in the stress response, the low muscle enzyme levels in both groups show that these immobilizing drugs and capture methods induce very little physical stress in moose. A hyperglycaemic response was found in MED-KET treated animals. Atipamezole hydrochloride (ATI) rapidly remobilized all animals and the time elapsing from ATI administration to standing was 3-9 ± 1.8 min after i.v./s.c. treatment (n=7) and 6.9 ± 3.4 min after i.m./s.c. injection (n=8). No side effects were detected after reversal. In conclusion, medetomidine-ketamine and atipamezole can be recommended for reversible immobilization of free-ranging moose in early autumn.